L-arginine Supplementation in Endurance Athletes: A Systematic Review of Recovery Mechanisms and Performance Enhancement - Karoń, Łukasz; Zygmunt, Anna Ewa; Karoń, Karolina; Grabowski, Wojciech; Drapała, Grzegorz; Pedrycz, Emilia; Pedrycz, Daria (Quality in Sport, 2024)
L-arginine, a semi-essential amino acid, has garnered significant attention for its potential to enhance athletic performance, particularly within endurance sports. Recognized for its multifaceted roles in cardiovascular, immune, and metabolic functions, L-arginine serves as a precursor to biologically active molecules, including nitric oxide (NO), creatine, and polyamines, which are integral to muscle function and recovery. Through its ability to stimulate NO production, L-arginine promotes vasodilation, enhancing blood flow and oxygen delivery to active muscles, thereby improving exercise efficiency and endurance. Additionally, L-arginine influences muscle protein synthesis (MPS) via activation of the mTOR signaling pathway, aids in ammonia detoxification within the urea cycle, and supports cellular energetics by facilitating ATP production. These mechanisms collectively underscore its potential to support prolonged physical exertion, reduce muscle fatigue, and expedite post-exercise recovery. This systematic review examines current evidence on L-arginine supplementation in endurance athletes, focusing on its physiological impacts, mechanisms of action, and potential to enhance recovery and performance. Despite promising findings, variability in individual responses and mixed results across studies highlight the need for refined dosing strategies and further research into long-term safety and efficacy. This review provides a comprehensive overview of L-arginine's potential as a supplement in sports nutrition, aiming to inform evidence-based recommendations for its application in endurance training and recovery strategies.